2021
DOI: 10.1002/bkcs.12353
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Phase Transition by the Enhanced Lattice Stability of Low‐Temperature Phase of Cr‐Doped VO2

Abstract: We have prepared Cr‐doped VO2 film (V1−xCrxO2, 0 ≤ x ≤ 0.15) on a c‐cut sapphire plate (0001). The insulator to metal transition (IMT) behavior of the VO2 was observed by the resistance and transmittance measurements near the phase transition point (Tc ~ 340 K). Whereas the starting point of metal to insulator transition (THE) was nearly constant at 350 K (x ≤ 0.03), the starting point of the insulator to metal transition (THS) was shifted from 308 K (x = 0) to 326 K (x = 0.05), suggesting that the Cr‐doped VO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Chromium can effectively stabilize the room temperature phase and thus raise the T MIT . 89–91 With Cr content increasing from 3.5% to 10%, T MIT is significantly raised from 80.8 to 111.5 °C (Fig. 4e).…”
Section: Influences Of Element Doping On Vo2mentioning
confidence: 93%
See 3 more Smart Citations
“…Chromium can effectively stabilize the room temperature phase and thus raise the T MIT . 89–91 With Cr content increasing from 3.5% to 10%, T MIT is significantly raised from 80.8 to 111.5 °C (Fig. 4e).…”
Section: Influences Of Element Doping On Vo2mentioning
confidence: 93%
“…The results of many studies have shown that external atoms generally reduce the phase transition amplitude of VO 2 by 1-2 orders of magnitude. 13,23,29,56,77,94,[101][102][103] Especially, for some elements, such as Cr, 91,101 H, 29 Ni, 103 and N, 76 a high doping level can even lead to the disappearance of the switch effects.…”
Section: Nanoscale Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The large scale and successful integration of VO2 for most of these applications require good control of the MIT characteristics (either electrical or optical) in one or more of its specific parameters: transition speed, magnitude, hysteresis width, and transition temperature value. These parameters can also be modified by doping the vanadium with metal atoms such as tungsten [16], magnesium [17], molybdenum [18], chromium [19], niobium [20] which results in a modulation of the Tc or a modification in a controlled way of the electrical or optical hysteresis shape. Thus, the material's properties can be adapted to a specific domain of applications requiring lower or higher transition temperatures, a precise hysteresis width, or particular electrical/optical properties in a specific state.…”
Section: Introductionmentioning
confidence: 99%